P-269 A Combination Therapy of Selective MMP9 Inhibitor and JAK Inhibitors Is Efficacious in Mouse DSS Model of Colitis. (February 2017) - Kim, Sunhwa; Carr, Brian; Tong, Leah; Sobczyk, Monika; Zheng, Jim; Lu, Bing; Mikaelian, Igor; Brockett, Robert; Jin, Debi; Wang, Ruth; Kanwar, Bittoo; Smith, Victoria
Abstract : Background: MMP9 (matrix metalloproteinase-9) promotes tissue destruction by degrading the basement membrane of epithelia and vasculature, in addition to driving inflammation via activation of cytokines and chemokines. MMP9 knock out animals were protected in dextran sulfate sodium (DSS)-induced colitis. A functional murine analog of the selective anti-MMP9 inhibitory antibody reduced disease activity index (DAI: stool consistency, hemoccults, and body weight change) in established chronic DSS colitis. A potent, selective, allosteric antibody that inhibits MMP9 is currently being investigated in clinical trials. Here, a combination therapy treatment with systemic anti-inflammatory agent, janus kinase (JAK) inhibitor, was investigated. Methods: Colitis was induced in female C57BL/6 (n = 15/group) and treatments were administered after the disease induction. Efficacy was assessed via metrics of colitis including DAI and histopathological measures. Also, MMP9 expression and activation of JAK pathway were evaluated. Two independent studies were conducted and similar results were obtained. The following analyses and results are from one study. Results: All animals were included in the evaluation. Treatment with each therapeutic agent, on its own or in combination, resulted in efficacy with respect to body weight change, stool consistency, hemoccults, colon length and weight, and histopathological assessment. Disease-induced body weight loss was improved in combination as compared to single agents (48% versus 21%–32%, relative to sham; P < 0.05 combination versus single agents). DAI score was lower in combination versus single agents (48% versus 73%–63%, relative to vehicle, P < 0.05). Normal stool consistency was better maintained in combination versus single agents throughout the study period (205% versus 139%–159%, relative to vehicle, P < 0.05). Drug treatment induced early disease control, with no disease at day 12 versus consistent disease symptoms in control-treated animals. The median ratio of colon weight/length (mg/cm) was 29 in combination versus 32 to 38 in single agents (40–42 in controls, P < 0.05). The median surface affected by erosion or atrophy inflammation was 19% in combination versus 38% to 41% in single agents (relative to vehicle, P < 0.05). Supportively, high MMP9 and high pSTAT3 (phosphorylated signal transducer and activator of transcription 3), indicating the activation of JAK pathway, were measured in active disease lesions and the signals were diminished in drug treated groups. Conclusions: The combination of anti-MMP9 inhibitory antibody with JAK inhibitor was significantly more effective than single agents to induce and maintain disease control by slowing disease progression and promoting mucosal healing. Further studies are required to examine combination therapy of selective anti-MMP9 antibody and JAK inhibitor in a clinical setting.